Removal of Arsenate From Groundwater by Cathode of Bioelectrochemical System Through Microbial Electrosorption, Reduction, and Sulfuration - Yuan, Honghong; Huang, Yumeng; Jiang, Ouyuan; Huang, Yue; Qiu, Dongsheng; Gustave, Williamson; Tang, Xianjin; Li, Zhongjian (Frontiers in Microbiology, 2022)
Arsenate (As(V)) is a toxic metalloid and has been observed at high concentrations in groundwater globally. In this study, a bioelectrochemical system (BES) was used to efficiently remove As(V) from groundwater and the mechanisms involved were systematically investigated. Our results showed that As(V) could be efficiently removed in BES cathode chamber. When a constant cell current of 30 mA (Icell, volume current density = 66.7 A/m3) was applied, 90 ± 3% of total As was removed at neutral pH (7.20-7.50). Whereas, when Icell was subsequently absent, the total As in effluent, mainly As(V), was significantly increased up to 2-3 times of the As(V) in influent. In abiotic control reactor, under the same condition, no significant total As or As(V) removal was observed. These suggest that As(V) removal was mainly ascribed to microbial electrosorption of As(V) in sludge. Moreover, part of As(V) was bioelectrochemically reduced to As(Ⅲ), and sulfate was also reduced to sulfides (S(−Ⅱ)) in sludge. The XANES results demonstrate that the produced As(Ⅲ) reacted with S(−Ⅱ) forming As2S3 precipitate and residual As(Ⅲ) was microbially electroadsorbed in sludge. This BES based technology does not require any organic or chemical additives and has a high As(V) removal efficiency, which makes it an environmental-friendly technique for As-contaminated groundwater remediation.